2017
DOI: 10.1088/1361-6595/aa8571
|View full text |Cite
|
Sign up to set email alerts
|

Modeling heat dominated electric breakdown in air, with adaptivity to electron or ion time scales

Abstract: We model heat dominated electrical breakdown in air in a short planar gap. We couple the discharge dynamics in fluid approximation with the hydrodynamic motion of the air heated by the discharge. To be computationally efficient, we derive a reduced model on the ion time scale, and we switch between the full model on the electron time scale and the reduced model. We observe an ion pulse reaching the cathode, releasing electrons by secondary emission, and these electrons create another ion pulse. These cycles of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…From Figure 4, it can be seen that the maximum temperature is consistent with that reported in the literature for similar discharge types [13,20,22,23]. An interesting difference between panels a and b in Figure 4 is that the maximum gas temperature, equal to 1,745 and 2,563 °C in panels a and b, respectively, is located at the middle of the discharge gap instead of the tip of the electrode as shown in panel a, which is in contrast to that shown in panel b and what is typically expected in such type of discharges20 22.…”
Section: Gas Temperature and Gas Rarefactionsupporting
confidence: 88%
See 1 more Smart Citation
“…From Figure 4, it can be seen that the maximum temperature is consistent with that reported in the literature for similar discharge types [13,20,22,23]. An interesting difference between panels a and b in Figure 4 is that the maximum gas temperature, equal to 1,745 and 2,563 °C in panels a and b, respectively, is located at the middle of the discharge gap instead of the tip of the electrode as shown in panel a, which is in contrast to that shown in panel b and what is typically expected in such type of discharges20 22.…”
Section: Gas Temperature and Gas Rarefactionsupporting
confidence: 88%
“…While multiple studies examined the spatial distribution of temperature in discharge configurations common for activating water [13,[20][21][22][23], very few focused on the temperature distribution in the liquid phase and its consequences on the gas phase, which is the focus of this work. To conduct this analysis, a numerical model developed in an earlier work of the group was upgraded to account for heat transfer and water vaporization at the plasma-liquid interface [24].…”
Section: Introductionmentioning
confidence: 99%
“…By coupling the fluid equations of discharge dynamics and the hydrodynamic equations for the air flow, Agnihotri et al observed that ambient air heats up to approximately 800 K within tens of nanoseconds within a mean ambient field of 17 kV/cm. This heating process and the induced pressure waves are effective enough to initiate electrical breakdown without the streamer mechanism with locally enhanced electric field tips (Agnihotri et al, 2017). Beyond air perturbations induced by shock waves and heating processes, civil transport aircraft, high-speed air vehicles, or the wind flow around (sharp) objects (Corda, 2017;Fleming et al, 2001;Gu & Lim, 2012;Gumbel, 2001;Lawson & Barakos, 2011) can initiate large pressure and thus air density gradients.…”
Section: Introductionmentioning
confidence: 99%
“…where the energy density S vt stored in vibrational states, is relaxed in τ vt = 20 µs [86]. The equation of states for perfect gases, p = (ρ g /m g )k B T, closes equations ( 8)- (10).…”
Section: Initial and Boundary Conditionsmentioning
confidence: 65%